2018
DOI: 10.1002/ange.201802713
|View full text |Cite
|
Sign up to set email alerts
|

Bulky Diamine Ligand Promotes Cross‐Coupling of Difluoroalkyl Bromides by Iron Catalysis

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Therefore, the development of superior LDs probe and study the physiological behavior of LDs become highly significant in biomedical research. 59,60 TPABSM is a superior liposoluble luminescent molecule, and the fluorine is a commonly used atom to improve the lipophilicity of drug molecules, 61,62 which thus inspired us to explore the possibility of TPABSM as a dye for LDs imaging. Before the experiment, we first calculated the logP (n-octanol/water partition coefficient) value of TPABSM because pioneering work has reported that organic dyes for lipid droplets staining usually exhibited logP value larger than 5 predicted by using QSAR (quantitative structure activity relations) models.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the development of superior LDs probe and study the physiological behavior of LDs become highly significant in biomedical research. 59,60 TPABSM is a superior liposoluble luminescent molecule, and the fluorine is a commonly used atom to improve the lipophilicity of drug molecules, 61,62 which thus inspired us to explore the possibility of TPABSM as a dye for LDs imaging. Before the experiment, we first calculated the logP (n-octanol/water partition coefficient) value of TPABSM because pioneering work has reported that organic dyes for lipid droplets staining usually exhibited logP value larger than 5 predicted by using QSAR (quantitative structure activity relations) models.…”
Section: Resultsmentioning
confidence: 99%
“…Hu and co‐workers reported a copper‐mediated aromatic 1,1‐difluoroethylation with Me 3 SiCF 2 CH 3 via “CuCF 2 CH 3 ” . Yamakawa and Zhang groups reported cobalt‐ and iron‐catalyzed difluoroalkylation of aryl Grignard reagents with CH 3 CF 2 Br, respectively (Scheme B).…”
Section: Methodsmentioning
confidence: 99%
“…We set out to explore 2-bromo-2,2-difluoroacetamides 1 in coupling reactions with aryl boronic acids 2 and (aryl)trialkoxysilanes 3 arylation agents as donors of aryl or heteroaryl substituents ( Scheme 1 a). We hypothesized ( Scheme 1 b) that using transition-metal-assisted catalysis, a 2-bromo-2,2-difluoroacetamide unit could undergo an oxidative addition on an appropriately tuned by ligands metal nuclei, forming an organometallic intermediate (structure 6 ) [ 35 , 36 , 37 ], followed by a rearrangement possibly via a CF 2 -carbene complex 7 , which undergoes loss of difluorocarben and simultaneous exchange of Br versus F giving rise to an organometallic (intermediate 8 ) capable of undergoing reaction with aryl boronic acids or aryl trialkoxysilanes to deliver a new intermediate ( 9 ), which after the reductive elimination would result in the formation of a new C-C bond to yield the desired aryl amide ( 5 ). An alternative mechanistic pathway could be via copper-intermediate 11 ( Scheme 1 c), as a result of the reaction between a fluorinated transition-metal catalyst and an aryl boronic acid (or aryl trialkoxysilane).…”
Section: Introductionmentioning
confidence: 99%